Investigation of Vibration Technique To Control Physical Properties of Yam Tubers (Dioscorea rotundata Poir) uring Storage - Osanyinpeju, Kifilideen L.; Aderinlewo, Adewole A.; Dairo, Olawale U.; Adetunji, Olayide R.; Ajisegiri, Emmanuel S.A. (Journal of Tropical Crop Science, 2022)
Yam tubers lose weight during storage and prolonged storage can reduce tuber quality and quantity. This study investigated the application of vibration techniques for the control of the physical properties of yam tubers during storage. Measurements were conducted on the physical properties of the tubers: weight loss, shrinkage of the middle diameter, shrinkage of the length, top and bottom diameter, on 108 tubers treated and 32 tubers untreated (control). The factors of the experimental design were three levels of vibration frequencies, i.e. low (1 – 5 Hz), medium (60 – 100 Hz) and high (150 – 200 Hz), amplitudes of low (5 mm), medium (10 mm) and high (20 mm), and durations of low (5 minutes), medium (10 minutes) and high (15 minutes). Tuber weights were classified as small (0.1 – 2.9 kg) and large (3.0 – 5.0 kg). The tubers were stored for ten weeks after vibration, and their physical properties were measured every week during the storage period. Our study demonstrated that as the frequency, amplitude, and duration of vibration increase, the physical properties of yam tubers decrease significantly in both tuber classes. The study shows that mechanical vibration can slow down the changes in the physical properties of the yam tuber during storage.